2022
DOI: 10.1007/s00431-022-04596-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased trend of thyroid cancer in childhood over the last 30 years in EU countries: a call for the pediatric surgeon

Abstract: Given the increasing incidence of thyroid cancer cases affecting the pediatric population in Europe, an epidemiological analysis of the available data is essential in order to update standards of care and recommend diagnostic and therapeutic strategies coherent to the new epidemiological trend. An observational study was conducted, considering the time interval 1991–2012, acquiring data collected by the International Agency for Research on Cancer (IARC) through the “Cancer Incidence in 5 continents plus” (CI5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…More recently, an observational study compared data collected by the International Agency for Research on Cancer (IARC) through the “Cancer Incidence in 5 continents plus” (CI5 plus) project with those of the latest report from the Global Cancer Observatory (GLOBOCAN 2020 project). An overall increasing prevalence of thyroid cancer was found in the age groups 10–19, with female late adolescents presenting a much higher incidence with respect to girls aged 10–14 years old ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, an observational study compared data collected by the International Agency for Research on Cancer (IARC) through the “Cancer Incidence in 5 continents plus” (CI5 plus) project with those of the latest report from the Global Cancer Observatory (GLOBOCAN 2020 project). An overall increasing prevalence of thyroid cancer was found in the age groups 10–19, with female late adolescents presenting a much higher incidence with respect to girls aged 10–14 years old ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the observed increased risk of DTC in postpubertal female subjects compared with their male counterparts include mechanisms involving female sex hormones, with estrogen and estrogen receptors (ERs) being the most investigated target of current research. Several in-vitro and animal studies have evaluated the influence of sex steroids on the proliferation of thyroid cells, although considerable discrepancies with respect to ER expression patterns in thyroid cancer tissues actually exist ( 43 , 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveillance data described 1.2 cases per 100,000 patients under the age of 20 but 0.4 cases per 100,000 in patients aged under 15 ( 31 ). However, the incidence of pediatric thyroid nodules and cancer appears to be steadily increasing and associated with a worse prognosis ( 32 ), far higher than the expected value in the adult population (5%) ( 33 ). In clinical practice, the management of pediatric thyroid nodules largely follows the adult thyroid guidelines ( 25 ), with some peculiarities related to pediatric age.…”
Section: Discussionmentioning
confidence: 99%
“…However, this should not include children younger than 18, and we have too few data on pediatric patients to draw accurate conclusions. Spinelli et al [ 58 ] indicated that thyroidectomy can be associated with a considerable rate of complications such as hypoparathyroidism and recurrent laryngeal nerve injury. For all of these reasons, they underline the necessity to develop specific management strategies for the pediatric population, in order to face the increasing rates of thyroid cancers in the pediatric field and to offer optimal surgical treatment and avoid unnecessary invasive approaches.…”
Section: Discussionmentioning
confidence: 99%